Colonization of helicobacter pylori in laryngeal pathologies among the patients in tertiary center - Bahadur Gurung, Lal; Maharjan, Rupa; Bahadur Pantha, Tridip; Gurung, Sarita; Bishankha, Dhiraj; Goudel, Bonu (Journal of Chitwan Medical College, 2024)
Background: Helicobacter pylori can cause a chronic infection and is linked to the development of benign and malignant aerodigestive tract diseases. This study aims to observe the colonization of helicobacter pylori in laryngeal pathologies. Method: A cross-sectional observational study was done among the cases undergoing surgery of the larynx at the Department of Otorhinolaryngology and Head and Neck Surgery in Bir Hospital, Nepal from 10 Aug 2020 to 15 Mar 2021. The specimen from the larynx was kept in a Rapid Urease Test dry test kit to observe the presence of H. pylori. The study was approved by the institutional review board. Data were analysed to find out the presence of H. Pylori in the samples, gastroesophageal reflux disease and colonization of Helicobacter, and benign vs malignant cases with Helicobacter. A p-value of <0.05 was considered statistically significant. Result: Out of 30 participants, benign pathology was 11 and malignant 19. H. pylori colonization was found in 6(20%), 2 in benign (2/11, 18.2%), and 4 in malignant (4/19, 21.1%) cases. The difference in H. pylori colonization between benign and malignant cases was statistically insignificant, (p=0.62). Conclusion: H. pylori colonization was found in 20% of larynx pathology, with no statistically difference among benign and malignant cases.